Special papersDistal neuroprotection system as option for right subclavian artery ostial recanalization - Misztal, Marcin; Pieniążek, Piotr; Zasada, Jakub; Brzychczy, Andrzej; Nessler, Jadwiga; Żmudka, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We present the case of a 49-year-old woman with neurological symptoms and severe atherosclerosis of aortic arch branches affecting subclavian and carotid arteries. Our patient has a history of transient ischemic attack and recurrent paresthesias of her right arm. We present a double access intervention using a distal embolic neuroprotection device during ostial right subclavian artery recanalization. We recommend that use of an embolic protection device in right subclavian artery ostial recanalization should be considered.